Contaminação Mercurial Em Peixes Do Rio Madeira: Resultados E Recomendações Para Consumo Humano - Padovani, Carlos R.; Forsberg, Bruce Rider; Pimentel, Tania P. (Acta Amazonica, 1995)
Samples of eleven fish species were collected during September and October of 1991 in the gold mining area of Cachoeira de Teotônio and in the control area Guajará-Mirim, along the Madeira River, (Rondônia, Brazil) and anaiized for total mercury by cold vapor atomic absorption spectrofotometry. Almost all fish predators from the gold mining area had mercury concentrations above the maximal level of 0.5 ug.g"1, permitted for human consumption by Brazilian Secretary of Health and the World Health Organization and much greater than those found in predatory fish species in the control area were all below this critical value (0.5 pg.g\'X demonstrating the influence of anthropogenic contamination in the gold mining area. In both areas, non-predators fish species had lower mercury concentrations than predators fish species, indicating the effects of biomagnification of mercury in the food chain. Safety limits for fish consumption by the human populations in this gold mining area were estabilished considering the mercury levels encontred in fish and the critical intake rate associated with the signs of mercury poisoning. Pacu, could be consumed without restrictions, matrinchã, curimatã, mandi and tucunaré, could be consumed with moderation and large predatory fish species (mostly Siluriformes), could be consumed only sporadically. Some factors that could influence mercury contaminations in "ribeirinhos" are discussed.
Mercury Concentrations in Fishes of the Madeira River: Results and Recomendations for Human Consumption
Keywords: Mercury; Hg; Gold-mining; Madeira River; Rondonia; Amazon; Fish; Mercúrio; Hg; Garimpo-de-ouro; Rio Madeira; Rondônia; Amazônia; Peixes